Elevated Tau in Military Personnel Relates to Chronic Symptoms Following Traumatic Brain Injury. Issue 1 (January 2020) - Pattinson, Cassandra L.; Shahim, Pashtun; Taylor, Patricia; Dunbar, Kerri; Guedes, Vivian A.; Motamedi, Vida; Lai, Chen; Devoto, Christina; Peyer, Jordan; Roy, Michael J.; Gill, Jessica M.
Abstract : Objective: To understand the relationships between traumatic brain injury (TBI), blood biomarkers, and symptoms of posttraumatic stress disorder (PTSD), depression, and postconcussive syndrome symptoms. Design: Cross-sectional cohort study using multivariate analyses. Participants: One hundred nine military personnel and veterans, both with and without a history of TBI. Main Measures: PTSD Checklist–Civilian Version (PCL-C); Neurobehavioral Symptom Inventory (NSI); Ohio State University TBI Identification Method; Patient Health Questionnaire-9 (PHQ-9); Simoa-measured concentrations of tau, amyloid-beta (Aβ) 40, Aβ42, and neurofilament light (NFL). Results: Controlling for age, sex, time since last injury (TSLI), and antianxiety/depression medication use, NFL was trending toward being significantly elevated in participants who had sustained 3 or more TBIs compared with those who had sustained 1 or 2 TBIs. Within the TBI group, partial correlations that controlled for age, sex, TSLI, and antianxiety/depression medication use showed that tau concentrations were significantly correlated with greater symptom severity, as measured with the NSI, PCL, and PHQ-9. Conclusions: Elevations in tau are associated with symptom severity after TBI, while NFL levels are elevated in those with a history of repetitive TBIs and in military personnel and veterans. This study shows the utility of measuring biomarkers chronically postinjury. Furthermore, there is a critical need for studies of biomarkers longitudinally following TBI. Abstract : Supplemental Digital Content is Available in the Text.